Ecological Structure, Diversity, and Utilisation Potential of Understory Vegetation in Sumber Arum Biodiversity Area, Banyuwangi - Nurchayati, Nunuk; As’ari, Hasyim; Ardiyansyah, Fuad; Dwi Daqsy, Irqami Rachma (Biotropika: Journal of Tropical Biology, 2026)
This study aimed to examine the ecological aspects and potential utilisation of understory vegetation in the biodiversity area of Sumber Arum, Songgon, Banyuwangi. The study was conducted using purposive sampling at five stations, which were further divided into 30 sub-stations in the areas of agroforestry, biodiversity park, home garden, riparian hillshade, and polyculture fields. Diversity data were analysed using the Shannon-Wiener index, while potential utilisation data were obtained through interviews with the local community and literature studies. The results showed that the understory vegetation comprised 30.818 individuals, 110 species, 104 genera, and 56 families. The highest abundance was found in home gardens, agroforestry, and riparian hillshades. The highest diversity and species richness were found in the polyculture field (H’: 3.04; R: 5.42) and home garden (H’: 2.92; R: 7.93). Understory vegetation was dominated by the grass Oplismenus compositum (27.4),  fern Diplazium esculentum (18.3), herb Soleirolia soleirolli (11.4) and Colocasia sp. (10.5), low shrubs Rubus fraxinifolius (7.4), shrubs Clidemia hirta (6.1), and liana Mikania micrantha (2.1). This vegetation has the potential to be used as food, medicine, spices, aromatics, ornamental plants, ground cover, and craft materials. Overall, it can be concluded that the understory vegetation found in the Sumber Arum Biodiversity Area in Songgon, Banyuwangi, has ecological and socioeconomic potential for the community.